The development of a zero-dimensional collisional-radiative model for interpreting plasma emission in low temperature divertor plasmas in tokamaks - Fox-Widdows, Ella; Bowden, Mark D.; Hoshino, Kazuo; Hatayama, Akiyoshi; Osawa, Ryoko; Tsubotani, Yuka (Frontiers in Physics, 2023)
Collisional-radiative models are commonly used to analyse atomic and molecular processes in low temperature plasmas by determining the distribution functions of excited states as functions of various plasma parameters. This paper outlines the improvements to a zero-dimensional collisional-radiative model, developed at Keio University, for purposes relevant to the analysis of emission measurements in low temperature hydrogen plasmas. The extension of this 0D model centres on the inclusion of additional molecular species and reactions, a calculation of emission intensity in order to directly compare with experimental work, and the addition of a simple wall model to allow for a deeper understanding of recycling of atoms and molecules in low temperature plasmas close to plasma facing components in fusion machines. Results from the improved model are then compared with both an existing CR model for benchmarking and experimental emission spectroscopy data from an inductively-coupled plasma device at the University of Liverpool. These results show how the developments to the model have increased the relevance to experimental plasmas, such as those in the power exhaust regions of fusion machines, with the ratio of the H β /Hα line intensities outputted from the improved CR model mirroring more closely the emission measured experimentally in the ICP device.